Periphytic diatoms from an oligotrophic lentic system, Piraquara I reservoir, Parana state, Brazil - Silva-Lehmkuhl, Angela Maria da [UNESP]; Tremarin, Priscila Izabel; Vercellino, Ilka Schincariol; Veiga Ludwig, Thelma A. (Revista Biota Neotropica, 2019)
Knowledge of biodiversity in oligotrophic aquatic ecosystems is fundamental to plan conservation strategies for protected areas. This study assessed the diatom diversity from an urban reservoir with oligotrophic conditions. The Piraquara I reservoir is located in an Environmental Protection Area and is responsible for the public supply of Curitiba city and the metropolitan region. Samples were collected seasonally between October 2007 and August 2008. Periphytic samples were obtained by removing the biofilm attached to Polygonum hydropiperoides stems and to glass slides. The taxonomic study resulted in the identification of 87 diatom taxa. The most representative genera regarding the species richness were Pinnularia (15 species) and Eunotia (14 species). Five species were registered for the first time in Brazil and seven in the State of Parana. Taxonomic and ecological comments of the species registered are provided.
Keywords: artificial substrate; diatom ecology; macrophytes; reservoirs